(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to describe the intrinsic and extrinsic structures of Imam Safwan’s poetry and analyze its relevance as literature teaching materials at SMA Negeri 1 Jereweh. The method used is descriptive qualitative with a Rene Wellek structuralism approach. The research subjects consisted of four selected poems: "Balada Dende Bayan," "Mencinta Mimpi, Nelayan Berwajah Sunyi," "Sore di Tanah Enda," and "Keriangan Pagi di Ujung Padi." Data collection was conducted through documentation studies analyzing the poems’ intrinsic and extrinsic elements. Data analysis techniques, through data verification stages, the next stage is data classification and comprehensive data interpretation. The results show that Imam Safwan’s poems possess a strong physical and spiritual structure, using authentic and poetic local diction. Extrinsically, these poems contain values ​​of local wisdom that reflect the agrarian and coastal life of the community. Furthermore, the relevance analysis indicates that these poems meet the criteria as literature teaching materials in the Independent Curriculum based on aspects of suitability to learning outcomes, sociocultural engagement, and students’ cognitive maturity levels. Therefore, this study recommends the use of Imam Safwan’s poetry as contextual teaching materials to enhance students’ literary appreciation and cultural literacy at SMA Negeri 1 Jereweh in the 2025/2026 academic year.